Human development 98/99. - Freiberg, Karen L. (Guilford : Dushkin/McGraw-Hill, 1998)
Annual Editions: Human Development 98/99 is organized according to the absolute time concept of chronos, chronological time, from conception through death.
Includes index.
Keywords: BEHAVIOR; CHILD DEVELOPMENT; DEVELOPMENTAL PSYCHOLOGY